1985
DOI: 10.1016/0272-0590(85)90172-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic toxicity and carcinogenicity studies of gentian violet in mice

Abstract: Gentian violet is a dye belonging to a chemical class known as the di- and triaminophenylmethanes. Although it has been used for many years for the control of fungal and intestinal parasites, for various uses in veterinary medicine, and as an additive to the feed of chickens to inhibit propagation of mold and fungus, very few long-term toxicity data are available. A life span dosing study of gentian violet in the diet of 720 males and 720 females of B6C3F1 mice (C57BL/6 X C3H) at dose levels of 0, 100, 300, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
3

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(38 citation statements)
references
References 11 publications
0
35
0
3
Order By: Relevance
“…However, triphenylmethane derivatives have been banned in almost all the world, mainly because of studies that revealed chronic toxicity and carcinogenicity of gentian violet in mice [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, triphenylmethane derivatives have been banned in almost all the world, mainly because of studies that revealed chronic toxicity and carcinogenicity of gentian violet in mice [9].…”
Section: Introductionmentioning
confidence: 99%
“…Malachite green is highly toxic to mammalian cells; it promotes hepatic tumor formation in rodents and also causes reproductive abnormalities in rabbits and fish (13,24). The structural similarity of malachite green to other carcinogenic triphenylmethane dyes also raises suspicion of carcinogenicity; gentian violet (crystal violet) is a thyroid and liver carcinogen in rodents (17), and pararosaniline is a bladder carcinogen in humans (7). Based on the potential for adverse human health effects, the U.S. Food and Drug Administration nominated malachite green as a priority chemical for carcinogenicity testing by the National Toxicology Program in 1993 (10).…”
mentioning
confidence: 99%
“…Hyperplastic changes in this tissue (including adenomas) have been reported in mice for structurally and functionally diverse chemicals [gentian violet (70), aniline dyes (120), misoprostol (go), nalidixic acid (6 l), and spontaneous incidence (103)l. The literature is sparse in the area of possible mechanisms ofhyperplastic lesions in this tissue. It is plausible that the hormone sensitivity of this gland may be related to a cell proliferation response.…”
Section: Pharmacologica~biochemical Effectsmentioning
confidence: 99%